TAFSIR `ILMI DALAM KITAB TAFSÎR AL-SYA`RÂWI - Muhammad Rizqi (Jurnal Ilmiah Al-Furqan: Al-qur'an Bahasa dan Seni, 2016)
This article discusses about Tafsir Ilmi. Tafsir Ilmi is a model of interpretation used by mufassir in translating Qur’anic Verses. The verses are categorized into sciences or scientific issues like creation of human beings and nature, rotation of sun, revolution of moon, and so forth. This model is also applied by Imam As-Sya’rawi in comprehending Quranic Verses. In this case, he explains scientific fields in more detail based on his knowledge and experience. Reading his interpretation, it can be seen that he has very large view. It makes his work different from other experts, and interest interpreters of tafsir. As-Sya’rawi’s tafsir is different from others because the mission and purpose of his tafsir are to express the wonder of al-Qur’an and the nature of iman. The book is not written in speech style and scientific writing, in spite of in teacher’s teaching method. It can be concluded that As-Sya’rawi’s large knowledge makes his scientific tafsir is different from other books of tafsir.